2000
DOI: 10.1597/1545-1569(2000)037<0017:taucpa>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Adult Unoperated Cleft Patient: Absence of Maxillary Teeth Outside the Cleft Area

Abstract: The results are in contradiction with the established hypothesis that absence of teeth outside the cleft area of the maxilla is due to an unknown congenital factor. On the contrary, the findings support the hypothesis that surgery for the closure of the hard palate in early childhood is the most important etiological factor for the absence of teeth outside the cleft area in the early operated cleft patient. The superficial position of the tooth germs (at the time of the palatal surgery), especially those of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 6 publications
2
13
0
4
Order By: Relevance
“…The prevalence of tooth agenesis among cleft patients is significantly higher (45-77%; 1, 6) than among noncleft patients (3.2-7.6%; 13). One reason for this may lie in specific surgical procedures, such as periosteoplasty or neonatal closure (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of tooth agenesis among cleft patients is significantly higher (45-77%; 1, 6) than among noncleft patients (3.2-7.6%; 13). One reason for this may lie in specific surgical procedures, such as periosteoplasty or neonatal closure (14).…”
Section: Discussionmentioning
confidence: 99%
“…The number of possible patterns for the upper or lower dental arch (excluding third-molar agenesis) equals 2 14 . Thirty-nine different patterns were found for the upper jaw.…”
Section: Agenesis Patterns In Upper and Lower Jawsmentioning
confidence: 99%
“…Three main factors might contribute to the increased prevalence of tooth agenesis in the BCLP patients. First, it has been hypothesized that specific surgical procedures, such as early periosteoplasty (21) or neonatal closure of the hard palate (22,23), might influence tooth formation because a lower prevalence of tooth agenesis was found in non-operated individuals with clefts (24). However, other studies have reported that surgical interventions do not seem to affect tooth agenesis (17).…”
Section: Discussionmentioning
confidence: 99%
“…C. Lekkas и соавт., проанализировав состояние зубочелюстной системы у 266 взрослых с неоперированными РГН, обнаружили у них исключительно низкий процент аплазии зубов и высказали предположение о влиянии на формирование зачатков зубов травматичной пластики неба в раннем возрасте [8]. В нашем исследовании из 35 детей с дефектом неба после уранопластики выраженная гипоплазия эмали постоянных резцов была обнаружена у 13 (37,1±7,4%), аплазия боковых резцов -у 18 (51,4±8,4%), аплазия центральных резцов -у 5 детей (14,3±5,9%).…”
Section: результаты и обсуждениеunclassified